Tax Compliance in Indonesian MSMEs: Key Factors Explored - Michael Michael; William Widjaja (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
This study investigates the factors that impact tax compliance in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on tax knowledge, tax sanctions, tax corruption, and information technology utilization. A survey of 200 MSMEs in Jakarta and SEM-PLS analysis found that tax knowledge does not significantly affect tax compliance. Tax sanctions proved to be a significant motivator for tax compliance, while tax corruption negatively eroded trust in the tax system. In addition, it was found that information technology moderates the effect of tax knowledge on compliance, suggesting the potential to improve tax understanding and simplify processes. The practical implication is the importance of implementing stricter tax penalties, the use of technology in tax education, and increased transparency in tax administration to mitigate corruption and encourage tax compliance among MSMEs. The findings provide theoretical contributions and practical implications in designing effective strategies to increase tax compliance and government revenue.